Hyponatraemia: clinical approach and therapy - Abreu, Fernando (2001)
Hyponatraemia is the most common electrolytedisturbance in hospitalised patients and it reflects awater balance disturbance with associated hypo-osmolality. There are several associated conditions:fluid losses, oedematous states (heart failure, hepaticcirrhosis, nephrotic syndrome), syndrome ofinappropriate anti-diuretic hormone secretion(SIADH), primary polydipsia and endocrinediseases. Initial evaluations to reach an aetiologicdiagnosis should include: measurement of plasmaticand urinary osmolality, the plasma concentration ofsodium, and clinical assessment of the extracellularcompartment. Two basic principles are involved inthe treatment of hyponatraemia: raising plasmasodium concentration at a safe rate and treating theunderlying cause. However, treatment of thisdisorder also requires balancing the risks ofhypotonicity against those of therapy, in order toavoid central osmotic demyelination. A new class ofpromising agents, the vasopressin receptorantagonists, has been described, and it seemsreasonable to expect improvement in the treatmentof hyponatraemia associated with heart failure,hepatic cirrhosis and SIADH.This article focuses on the causes, differentialdiagnosis and treatment of this electrolyte disorder.